The Effect of Kahoot! Software on Students’ Vocabulary Mastery for Elementary Students: A Literature Study - Isnaniah Isnaniah; Nur Hasanah Lutfi (Journal of Excellence in English Language Education, 2022)
Kahoot! is a game-based learning (GBL) platform and used to know students’ knowledge, for formative assessment or as a break from traditional and monotonous classroom activities. The aim of this research was to investigated whether there is students’ positive perspective and significant effect after used of Kahoot! on students’ vocabulary mastery for elementary students. Many studies have been published on the effect of using Kahoot! in the classroom activities. This research presents the result of a literature review on the effect of using Kahoot! for learning, specifically on students’ perspective and learning process. The literature review includes 220 studies, but it’s including duplicated journals that did not match with the inclusion criteria were excluded. The 15 studies used and found out that after the use of Kahoot! students’ and teachers have a positive perspective and it shows the significant effect on learning vocabulary mastery. However, there are also some studies where the use of Kahoot! Has little or no significant effect. The most challenges mentioned by students’ commonly the technical issue such as unreliable internet connection, stressful time pressure when they try to find the answers some students’ have failing quiz experience and teachers’ find it challenging to deal and work together with the technology.